A A SYSTEMATIC LITERATURE NETWORK ANALYSIS (SLNA) : SCHOOL-UNIVERSITY PARTNERSHIPS (SUPS) AND FUTURE RESEARCH AGENDA - I Nyoman Try Upayogi; Riandi; Sumar Hendayana; Ida Kaniawati (International Journal of Instructions and Language Studies, 2023)
This study aims to uncover current, trending, and future research areas within School-University Partnerships (SUPs). The research employs the Systematic Literature Network Analysis (SLNA) method, combining Systematic Literature Review (SLR) using the PRISMA protocol and Bibliometric Analysis with VOSviewer software. The findings indicate a consistent annual increase in SUPs publications, with the United States dominating the research landscape. The VOSviewer analysis reveals key research topics: pre-service teachers, initial teacher education, teacher education in Cluster 1, professional development and school-university partnerships in Cluster 2, and educational development, teacher training, and university in Cluster 3. Overlay Visualization highlights current research trends, including pre-service teachers, professional experience, professional learning community, professional learning, curriculum, learning communities, and communities of practice. Thematic evolution mapping suggests future research involving pre-service teachers in SUPs, such as exploring communities of practice. This research provides valuable guidance for SUPs researchers in selecting and determining future research topics, facilitating informed and strategic contributions to the field.